HUBUNGAN SANITASI LINGKUNGAN DENGAN KEJADIAN DIARE PADA BURUH TANI KKPA KELURAHAN SUNGAI PAGAR KECAMATAN KAMPAR KIRI HILIR: Environment Sanitation Relationship with Diarrhea Events in Water Tanking KKPA Pattern Sungai Pagar Village Kampar Kiri Hilir Sub-District - Kampar - M. Kamali Zaman (STIKes Al-Insyirah Pekanbaru, 2019)
Diarrhea is the second highest disease in Indonesia. Diarrhea disease is one of contagious diseases which until now is still a health problem for some people in Riau Province, even often become extraordinary incident.This research uses quantitative research type with cross sectional analytic design. This research was conducted in Sungai Pagar village Kampar Kiri Hilir sub-district on May - June 2017, with sample number 73 family head (KK). The data were collected by using questionnaire and checklist. Data analysis for bivariate with chi-square test at α = 0,05. The results of this study indicate that there is a significant relationship between latrines with the incidence of diarrhea with pvalue = 0.002,There is a significant relationship between wastewater disposal with the incidence of diarrhea with pvalue = 0,024,There is a significant relationship between waste sanitation with the incidence of diarrhea with pvalue = 0,029,There is a significant relationship between the of the house with the incidence of diarrhea with pvalue = 0.035.It can be concluded that there is a significant relationship between latrine, waste water disposal, waste sanitation and the characteristics of the house with the incidence of diarrhea in Sungai Pagar Village in 2017. Suggested to related parties As as input and socialization for farm laborers in sungaipagar village About the of condition latrines, sewerage, sanitation of garbage and of the house against the incidence of diarrhe diseases, so it is expected there is awareness of farm kaborers in Sungai Pagar village To follow a clean and healthy lifestyle.